Employee Onboarding in an Organization Using Servicenow - Maganty, Chandra Sekhar; Vijaya, Korlipara Satya; Ravipati, Sindhuja; Mallidi, Suma; Prasanthi, K Sai (International Journal of Psychosocial Rehabilitation, 2020)
Consistently, a large number of people start an occupation with another association. A fundamental objective for associations is to get their new workers ready for action both rapidly and easily, so they can add to authoritative achievement. New workers must learn both the social and undertaking related parts of their employments just as the social and hierarchical related parts of their new association. To encourage their prosperity, a framework ought to be set up to help sort out the procedure, data trade, and modification of fresh recruits. Finding the best contender for positions in an association is just a piece of building a viable group. The procedure of onboarding new representatives can be one of the most basic factors in guaranteeing profits. In any case, more often, onboarding is frequently mistaken for orientation. While orientation may be important administrative work and other routine errands must be finished. Onboarding is the process including the board and different representatives that can last as long as a year.